Navigating the Epistemic Responsibilities of Individuals and Institutions for Sustainability - Pennacchioni, Giulio (Filosofia Morale/Moral Philosophy, 2024)
This paper delves into individual and institutional epistemic responsibilities on climate change and sustainability. It highlights the challenges individuals face in understanding climate information and emphasizes the pivotal role of intergovernmental institutions and states as “epistemic facilitators”. Despite the meritorious efforts of organizations such as UNESCO in this sense, only states and institutions can fulfill the epistemic responsibility of sharing accurate climate change information, educating citizens and consumers, and implementing sustainable policies.